Densification, microstructure, and mechanical properties of V-substituted HfB2-based ceramics. Issue 2 (15th January 2021) - Zhu, Qi-Qi; Guo, Wei-Ming; Lin, Hua-Tay
Abstract: This study firstly developed Hf1-x Vx B2 (x = 0, 0.01, 0.02, 0.05) powders, which were derived from borothermal reduction of HfO2 and V2 O5 with boron. The results revealed that significantly refined Hf1-x Vx B2 powders (0.51 μm) could be obtained by solid solution of VB2, and x ≥ 0.05 was a premise. However, as the content of V-substitution for Hf increased, Hf1-x Vx B2 ceramics sintered by spark plasma sintering at 2000 °C only displayed a slight densification improvement, which was attributed to the grain coarsening effect induced by the solid solution of VB2 . By incorporating 20 vol% SiC, fully dense Hf1-x Vx B2 -SiC ceramics were successfully fabricated using the same sintering parameters. Compared with HfB2 -SiC ceramics, Hf0.95 V0.05 B2 -20 vol% SiC ceramics exhibited an elevated and comparable value of Vickers hardness (23.64 GPa), but lower fracture toughness (4.09 MPa m 1/2 ).